Knockdown of lncRNA LINC01234 Suppresses the Tumorigenesis of Liver Cancer via Sponging miR-513a-5p - Xu, Wen; Li, Kesang; Song, Changfeng; Wang, Xiaotong; Li, Yueqi; Xu, Baixue; Liang, Xin; Deng, Wanli; Wang, Junqing; Liu, Jianwen (Frontiers in Oncology, 2020)
Background: Liver cancer is a frequent malignancy with poor prognosis and high mortality all over the world. It has been reported many lncRNAs could modulate the tumorigenesis of liver cancer. To identify novel potential targets for liver cancer, the differential expressed lncRNAs between liver cancer and adjacent normal tissues was analyzed with bioinformatics tool. Methods: The differential expressed lncRNAs between liver cancer and adjacent normal tissues were analyzed with bioinformatics tool. Cell viability and proliferation was tested by CCK8 and Ki67, respectively. Apoptosis of liver cancer cells was tested by flow cytometry. Gene and protein expressions in liver cancer cells were measured by qRT-PCR and western blot, respectively. In vivo model of liver cancer was established to detect the effect of LINC01234 on liver cancer in vivo. Results: LINC01234 was found to be negatively correlated with the survive rate of patients with liver cancer. Moreover, knockdown of LINC01234 significantly suppressed the proliferation and invasion of liver cancer cells via inducing the apoptosis. Meanwhile, miR-513a-5p was sponged by LINC01234, and USP4 was found to be a direct target of miR-513a-5p. In addition, LINC01234 knockdown inhibited the tumorigenesis of liver cancer via inactivating TGF-β signaling. Furthermore, silencing of LINC01234 notably inhibited the tumor growth of liver cancer in vivo. Conclusion: Downregulation of LINC01234 could inhibit the tumorigenesis of liver cancer via mediation of miR-513a-5p/USP4/TGF-β axis. Thus, LINC01234 might serve as a new target for the treatment of liver cancer.